If Gold Is Our Destiny: How a Team of Mavericks Came Together for Olympic Glory - Murray, Sean P., (Rowman & Littlefield Publishers, 2022)
The true story of how a group of talented volleyball players learned to put their egos aside, became a team, and changed the sport of volleyball forever. In the early 1980s, a golden generation of volleyball players joined the U.S. men’s national team. With the Olympics coming to Los Angeles in 1984, the pressure was on to build a winning program around these exceptional athletes. But could a group of individuals put aside their egos and play as a true team to achieve Olympic gold in their home country? In If Gold Is Our Destiny: How a Team of Mavericks Came Together for Olympic Glory, Sean P. Murray shares the incredible story of how a group of free-spirited players and their demanding coach captured the heart of a nation and became one of the greatest indoor volleyball teams of all time. As the team struggled leading up to the Olympics, head coach Doug Beal mandated a highly controversial three-week Outward Bound hike across one hundred miles in the Canyonlands and Abajo Mountains in Utah. Murray details all the internal strife and heartwarming triumphs from this unprecedented trip, as players and coaches learned to cooperate and trust one another. He reveals how the team used this newfound trust to implement an innovative approach to volleyball that changed not only their success on the court but the sport itself on a global scale. Featuring original interviews with players, coaches, and staff, along with a foreword by three-time gold medal champion Karch Kiraly, If Gold Is Our Destiny delivers an inside look at what it takes for a group of talented individuals to overcome their differences, build a culture of excellence, and become the best in the world.